IDENTIFIKASI BAKTERI Escherichia coli SUBTIPE Enteroaggregative Escherichia coli DAN Enteropathogenic Escherichia coli DENGAN METODE KULTUR DAN POLYMERASE CHAIN REACTION PADA SATE DAGING BABI DI KOTA DENPASAR - Putra, I Dw. Gd. Bayu Artha Pratama; Sukrama, I Dewa Made; Budayanti, Ni Nyoman Sri; Hendrayana, Made Agus (E-Jurnal Medika Udayana, 2022)
ABSTRACT Pork satay is a traditional Balinese dish whose basic ingredient is pork. Pork contains Escherichia coli bacteria which is a normal flora in pigs, so if it is not processed properly and hygienically, it has the potential to be contaminated with Escherichia coli bacteria from pork or in the processing process which can cause diarrhea if consumed. This study aims to identify the presence of Escherichia coli bacteria contamination as well EAEC and EPEC subtypes on pork satay in Denpasar City. This research is a descriptive study with an observational research design. In this study, using cluster purposive sampling technique with 16 samples taken from each sub-district in Denpasar City. All samples were examined at the Microbiology Laboratory, Faculty of Medicine, Udayana University. The samples were cultured on Eosin Methylene Blue Agar (EMBA) media and the positive results of Escherichia coli bacteria from the culture process were continued to the identification stage using the Polymerase Chain Reaction (PCR) method. Of the 16 samples of pork satay tested for culture, 9 (56%) samples were positive for Escherichia coli bacteria. All positive samples were continued with the identification process using the Polymerase Chain Reaction (PCR) method and the results showed no one of EAEC and EPEC subtypes were detected in all positive samples. In this study, most of the pork satay samples were contaminated with Escherichia coli bacteria, but after molecular identification, no one of EAEC and EPEC subtypes were found in all samples that were positive for Escherichia coli bacteria. Keywords : Pork satay, Escherichia coli, Diarrhea